Application and Development of an Environmentally Friendly Blast Hole Plug for Underground Coal Mines - Donghui Yang; Yixin Zhao; Zhangxuan Ning; Zhaoheng Lv; Huafeng Luo (Shock and Vibration)
Drilling and blasting technology is one of the main methods for pressure relief in deep mining. The traditional method for blasting hole blockage with clay stemming has many problems, which include a large volume of transportation, excess loading time, and high labor intensity. An environmentally friendly blast hole plug was designed and developed. This method is cheap, closely blocks the hole, is quickly loaded, and is convenient for transportation. The impact test on the plug was carried out using an improved split Hopkinson pressure bar test system, and the industrial test was carried out in underground tunnel of coal mine. The tests results showed that, compared with clay stemming, the new method proposed in this paper could prolong the action time of the detonation gas, prevent premature detonation gas emissions, reduce the unit consumption of explosives, improve the utilization ratio, reduce the labor intensity of workers, and improve the effect of rock blasting with low cost of rock breaking.